The detection and management of suspected cephalopelvis disproportion in the African primigravida by cervicographic analysis - Philpott, R H (Robert Hugh), 1927- (Not Specified, 2024)
The .Medical School in the .University of Rhodesia is one of the newer Schools in Af.rioa, with its first class having graduated in 1968. The author is the first oooupant of the Chair of Obstetrics and Gynaecology and was appointed in 1966. When considering a policy for the establishment of both personal and departmental research work, it was felt that certain factors and principles should be taken into consideration. Firstq, this is the only medical school in Rhodesia and, recognising the size and isolatiod, of the country, financial resources for research would be fairq limited. Secondq, research I ' interests should be directed to the particular clinical pt"oblems of Central Africa, rather than to subjects that could be better tackled in the well-equipped laboratories of developed countries. It would be important not on~ to study the ma.jar relevant clinical problems, but also to pt"epare regimes of di88Uosis and management which would be aui ted to the pcsormel and facilities available throushout the whole oountry. Once these regimes bad been evolved and taU&ht, the task would be completed by evaluating their practical application in both I central and peripheral uni ts.